Characteristics of MD2 Pineapple Leaf Kraft Pulp and Paper Blended with Recycle Carton Box - Sabri, Shahiran Nasirudeen; Masrol, Shaiful Rizal; Mohamad Firdaus Saat,; Norsahidah Abdullah, (Progress in Engineering Application and Technology, 2025)
The increasing environmental impact of traditional papermaking, primarily due to deforestation and high resource consumption, necessitates the exploration of sustainable alternatives. This study investigates the potential of MD2 pineapple leaf fiber as a non-wood-based raw material for papermaking, blended with a recycled carton box (RCB). The primary objectives are to produce liner paper from MD2 pineapple leaf kraft pulp blended with RCB and evaluate its physical and mechanical characteristics. Five blend proportions were tested in this study: 100% MD2, 75% MD2 and 25% RCB, 50% MD2 and 50% RCB, 25% MD2 and 75% RCB, and 100% RCB. The methodology involves preparing MD2 pineapple leaf pulp and RCB, followed by the soda-AQ pulping process. Laboratory papermaking procedures were employed to produce paper sheets, which were subjected to various physical and mechanical tests, including tensile strength, tear resistance, burst strength, and folding endurance, in accordance with TAPPI and MSISO standards. The results reveal an increasing trend in tensile strength, tearing resistance, and folding endurance as RCB content increases. Conversely, MD2 enhances burst strength across the blends, with the 25% MD2 and 75% RCB blend identified as the most optimal due to its balanced physical and mechanical properties. This research highlights MD2 pineapple leaf fiber as a viable alternative raw material, offering significant environmental benefits and contributing to sustainable papermaking practices.